(untitled) (TAJ: Journal of Teachers Association, 2010)
This was a hospital based study done to see the demographic profile of patients with metabolic syndrome in Bangladesh. A total of 334 patients attending in medicine OPD BSMMU were included in this study. According to modified NCEP ATP III criteria 27.2% of subjects aged ≥ 20 years had the metabolic syndrome and it was more commonly seen in women than in men (32.4% vs 21.7%). The metabolic syndrome increased with age in both sexes (40-49 years age groups 24.2% to 50-59 years age groups 35.2%). The metabolic syndrome was also significantly associated with postmenopausal period, family income, leisure time exercise (<60 min/wk), low physical activity, self reported high intake of carbohydrate diet, presence of family history and past history of components of the metabolic syndrome. DOI: 10.3329/taj.v22i1.5018 TAJ 2009; 22(1): 36-42